2012
DOI: 10.1016/j.psyneuen.2011.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Chronic juvenile stress produces corticolimbic dendritic architectural remodeling and modulates emotional behavior in male and female rats

Abstract: Nearly 12% of US children are exposed to intense adverse experiences. Research has demonstrated that these experiences can negatively impact adult health, often resulting in psychopathology. Less attention, however, is given to the impact of childhood adverse experiences on childhood health and wellbeing. Using a rodent model of chronic juvenile stress (restraint 6h daily from postnatal day 20–41), we report that chronic stress has significant immediate morbidities in both males and females during this develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
169
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(188 citation statements)
references
References 40 publications
17
169
0
1
Order By: Relevance
“…While stress effects in the BNST morphology seem more similar, since different types of stress induce a general hypertrophy of dendrites in the neurons of this brain region (Pego et al 2008;Vyas et al 2003), the effects of stress in the amygdala are less concordant to our present observation of dendritic atrophy. Whereas chronic juvenile stress leads to a general hypertrophy of amygdalar dendrites (Eiland et al 2011), others failed to find any significant change in dendritic structure after stress exposure in adulthood (Pego et al 2008) and others have shown remarkably divergent changes in amygdalar neurons following different types of stress (Vyas et al 2003;Vyas et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…While stress effects in the BNST morphology seem more similar, since different types of stress induce a general hypertrophy of dendrites in the neurons of this brain region (Pego et al 2008;Vyas et al 2003), the effects of stress in the amygdala are less concordant to our present observation of dendritic atrophy. Whereas chronic juvenile stress leads to a general hypertrophy of amygdalar dendrites (Eiland et al 2011), others failed to find any significant change in dendritic structure after stress exposure in adulthood (Pego et al 2008) and others have shown remarkably divergent changes in amygdalar neurons following different types of stress (Vyas et al 2003;Vyas et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Both chronically stressed males and females exhibited anhedonia, increased locomotion when exposed to novelty, and altered coping strategies when exposed to acute stress. Chronic stress produced shrinkage of dendrites in the hippocampus and PFC and concurrent hypertrophy of dendrites in the amygdala, with a trend for males to show more robust responses than females (Eiland et al, 2012).…”
Section: Emergence Of Sex Differences In Response To Stressors Aftermentioning
confidence: 99%
“…Demonstration of this was accomplished using a rodent model of chronic restraint stress in juvenile rats daily from postnatal days 20 to 41 (Eiland et al, 2012). Chronic stress produced depressivelike behavior and significant neuronal remodeling of brain regions likely involved in these behavioral alterations: the hippocampus, PFC, and amygdala.…”
Section: Emergence Of Sex Differences In Response To Stressors Aftermentioning
confidence: 99%
“…Neurochemically, altered DA levels have been reported in patients and animal models of depression and schizophrenia (Reynolds 1983;Kapur and Mann 1992;Yadid et al 2001;Dunlop and Nemeroff 2007;Heinz and Schlagenhauf 2010;Niwa et al 2010). Anatomically, in stress-induced depressive animals, changes of neuronal morphology in the mesocorticolimbic system are noted (Shansky and Morrison 2009;Eiland et al 2011). In the BLA, the pyramidal neurons develop exuberant dendritic arbors in response to stress (Vyas et al 2002).…”
Section: Introductionmentioning
confidence: 99%